Plasma-catalytic system with narrow-aperture rotating gliding discharge - Nedybaliuk, O.A.; Tyshchuk, P.V.; Tereshchenko, T.A.; Fedirchyk, I.I. (Вопросы атомной науки и техники, 2021)
The article presents the results of the investigation of the rotating gliding discharge with the narrow aperture in the airflow. The photographs of the rotating gliding discharge with the narrow aperture were matched with its voltage oscillograms. Photographs were used to determine the maximum length of the discharge channel and its dependence on the airflow Gd into the discharge chamber. Voltage oscillograms were used to determine the difference between the maximum and minimum discharge voltage ΔU = Umax-Umin. The dependence of the electric field in the positive column on the airflow Gd into the discharge chamber was plotted. Optical emission spectra of the plasma of the rotating gliding discharge with a narrow aperture were captured and used to determine the distribution of the vibrational Tv and rotational Tr temperatures along the length of the plasma torch inside the reaction chamber.